Tradition, ritual, and art of the Baliatn; The conceptualization of philosophy and the manifestation of spirituality among the Dayak Kanayatn - Olendo, Yudhistira Oscar; Dewantara, Jagad Aditya; Efriani, Efriani (Wacana, Journal of the Humanities of Indonesia, 2022)
Rapid globalization has slowly eroded the survival of the Baliatn ritual of the Dayak Kanayatn. Nowadays, the locals only rarely perform this ritual which is a manifestation of their culture. This study describes the Baliatn ritual pointing out it is pregnant with the meaningful philosophy of the ancestors. This tradition sets out the relationship between the people and nature; an example of gratitude and spirituality in this modern era. It also discusses the importance of cultural conceptualization through philosophy, art, and spirituality. Importantly, the Baliatn is an expression of the Dayak Kanayatn idea of how to live and appreciate life. They believe their closeness to nature allows them to create a harmonious relationship with God. This culture is founded on ancestral traditions, including literature, art, music, and incantations. The writers claim that a good description of the Baliatn is essential because it is nearly extinct. They are continuing their research on the Baliatn ritual